Análise comparativa das instituições e organizações agroindustriais citrícolas dos estados da Flórida (EUA) e São Paulo (Brasil) - Gaban, Luiz Carlos (Universidade Federal de São Carlos, 2008)
Starting with citrus introduction in both Americas, citrus agro industry system installed in Florida (USA) and São Paulo (Brazil) suffered deep changes during growth and evolution processes. Changes caused by new technologies and unexpected events shaped the structure of these systems. Differences of cultural characteristics and habits of each region influenced the structure and model of coordination existent in each system as well as the intensity of State presence. North America cultural traces drove to organizations of education, research and extension that helped the creation of new products, organizations of interest defense and mechanisms of control that, with the State intervention, resulted in laws, rules and organizations that currently control the whole citrus productive chain in Florida. Unexpected events caused distinct effects in each system. The Second World War caused positive changes in the Florida s system and negative in São Paulo s one. Frost of 1962 was responsible for a negative effect in Florida and a positive one in São Paulo. This work aims to analyze historical process and main organizational aspects of the decision chain regarding the system installed in Florida and São Paulo. Also to, identify impacts of changes on institutional environment, due to embedded habits in each region and by the State action, on relationship among actors of these systems, government mechanisms and coordination ways. For this it was used theoretical references from institutionalism. These contributions permitted to apply routers that could make possible analysis of vertical and horizontal coordination of all system links.
Keywords: Cítricos; Cadeias agroindustriais coordenação; Economia institucional; Sistemas agroindustriais; Citrus; Coordination; Institutional; Agro industry systems; ENGENHARIAS::ENGENHARIA DE PRODUCAO